Spatial effect of innovation efficiency on ecological footprint: City-level empirical evidence from China - Ke, Haiqian; Dai, Shangze; Yu, Haichao (Environmental technology & innovation, 2021)
Improving the level of innovation is a driving force for the sustainable development of urban economy, ecology and society. Improved data envelopment analysis (DEA) is used herein to investigate 280 cities in China and measure their innovation efficiency during 2012–2018, and a spatial measurement model is applied to analyse the impact of innovation efficiency on ecological footprint. In addition, this paper further discusses the impact of innovation efficiency on ecological footprint of different regions, comparing innovative and non-innovative cities, and eastern, central and western cities. The major findings are as follows: (1) A significant positive spatial relationship exists in the ecological footprint of Chinese cities as a whole, including eastern and central cities. (2) Promoting innovation efficiency significantly inhibits the ecological footprint of not only local region, but also neighbouring regions, with coefficients of −0.2488 and −0.1638 respectively. (3) The inhibitory effect of the increase in innovation efficiency in innovative cities on ecological footprint is stronger in local and neighbouring regions than non-innovative cities. In eastern and central Chinese cities, local ecological footprint is subject to a potent inhibitory effect from the progress in innovation efficiency, while the improvement in innovation efficiency has shown a significant promoting effect in the western region; and the ecological footprint of neighbouring regions only in the eastern cities is inhibited by the improvement of innovation efficiency of local regions. •Adopts the improved data envelopment analysis (DEA) to investigate 280 cities in China.•Applies the spatial measurement model to analyse the impact of innovation efficiency on ecological footprint in China.•Uses the dynamic spatial measurement model to re-examine the relationship between innovation and the ecological footprint in China.•Discusses the spatial impact of innovation efficiency on ecological footprint of different regions in China.